Effects of paramylon‐rich Euglena gracilis EOD‐1 powder on visceral fat obesity in moderately obese Japanese adults: A randomized, double‐blind, placebo‐controlled, parallel‐group trial. Issue 2 (17th November 2022) - Aoe, Seiichiro; Kawano, Takanori; Naito, Junko; Nishida, Norihisa; Takahashi, Madoka
Abstract: To investigate whether supplementation of paramylon (PM)‐rich Euglena gracilis EOD‐1 powder (EOD‐1) reduces visceral fat obesity in moderately obese Japanese subjects. A randomized, double‐blind, placebo‐controlled intervention study was conducted involving 36 Japanese adults with a body mass index (BMI) ≥25 and <30 kg/m 2 . Subjects were randomly assigned into two groups to consume EOD‐1 capsules (EOD‐1 group, 2.6 g PM/day) or cellulose capsules (placebo group) for a 12‐week period. Anthropometric measurements including visceral fat area (VFA) and blood samples were measured at baseline and throughout the trial. There was no significant difference in VFA between the two groups, although subgroup analysis by gender showed a significant decrease in VFA in the male EOD‐1 group compared with the placebo group. Serum adiponectin levels in all subjects from the EOD‐1 group were significantly higher than in the placebo group. By comparison with the placebo group, the subjects in the EOD‐1 group showed a significant reduction in serum HbA1c levels. EOD‐1 intake led to a significant reduction in VFA in male subjects with moderate obesity (BMI 25–30 kg/m 2 ). PM in EOD‐1 may contribute to preventing visceral fat obesity in male Japanese subjects. Moreover, PM may also contribute to improving glucose homeostasis in moderately obese Japanese adults. Abstract : We studied whether paramylon‐rich Euglena gracilis EOD‐1 powder supplementation could improve visceral fat obesity. EOD‐1 was found to enhance VFA loss and increase serum adiponectin concentration in moderately obese male adult subjects after a 12‐week supplementation period (2.6 g/day PM). EOD‐1 may reduce the serum HbA1c concentration and HOMA‐R in both male and female subjects. Effect of PM EOD‐1 on visceral and subcutaneous fat areas (bars represent mean and SE). *: p < .05 (vs. baseline, paired t ‐test), #: p < .05 (ANCOVA). □ baseline, ■ 12 weeks.